MAPPING RESEARCH TRENDS IN MOTIVATION AND SELF-CONFIDENCE FOR OBESE PRIMARY SCHOOL STUDENTS: A BIBLIOMETRIC PERSPECTIVE - Muhd Saufi Razman; Mohd Syaubari Othman; Mohd Yahya Fazly; Asnida Ismail; Wan Azani Mustafa; Rozitah Razman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Research on motivation, self-confidence, and physical well-being among obese primary school students in physical education has grown substantially over the past two decades, reflecting heightened concern over childhood obesity and its impact on students’ physical and psychological health. Analysis of publication trends from 2004 to 2024 reveals that the topic gained traction in 2012, reaching a peak between 2016 and 2018, with research contributions largely from the United States, followed by countries like Australia and the United Kingdom. A total of 1,041 documents were analyzed, with key contributors and highly cited works identified, showcasing influential studies focused on physical education interventions and psychosocial well-being. Using Scopus Analyzer and VOSviewer software, the study mapped co-authorship networks, identifying the top 10 authors and revealing collaborative trends that support an interdisciplinary approach to obesity research in educational contexts. Keywords such as "obesity," "physical activity," "self-confidence," and "motivation" emerged as prevalent, reflecting central themes in understanding and addressing obesity through school-based physical education. Numerical findings indicate strong co-authorship connections among authors and high citation counts for works emphasizing active interventions and mental health support in physical education curricula. These findings suggest a sustained need for evidence-based strategies to foster both physical and psychological resilience in obese primary school students, highlighting the importance of continued global collaboration in this field. The results provide valuable insights for future research directions, emphasizing comprehensive approaches to improve the well-being of students through targeted, interdisciplinary physical education initiatives.